Diversity Management: A New Organizational Paradigm - Gilbert, Jacqueline A. (Journal of business ethics, 1999)
Currently, an increasing number of organizations are attempting to enhance inclusiveness of under represented individuals through proactive efforts to manage their diversity. In this article, we define diversity management against the backdrop of its predecessor, affirmative action. Next, selected examples of organizations that have experienced specific positive bottom line results from diversity management strategies are discussed. The present paper also provides a conceptual model to examine antecedents and consequences of effective diversity management. Additional research areas identified from the model and literature review result in a number of research propositions intended to enhance the exploration and understanding of diversity management.